Acute Keratoconjunctivitis Resulting From Coinfection With Avian Newcastle Virus and Human Adenovirus. Issue 5 (3rd May 2022) - Prajna, N. Venkatesh; Lalitha, Prajna; Chen, Cindi; Zhong, Lina; Lietman, Thomas M.; Doan, Thuy; Seitzman, Gerami D.
Abstract : Purpose: The aim of this study was to report a case of human keratoconjunctivitis caused by both Newcastle disease virus (NDV) and human adenovirus. Methods: A 32-year-old-man presented with an acute unilateral keratoconjunctivitis that resolved with corneal scarring. On presentation, his conjunctival swab was collected for metagenomic sequencing. Results: The highest number of pathogen sequencing reads in the conjunctival sample mapped to the NDV. The second highest number of reads mapped to human adenovirus. Confirmation testing with directed reverse-transcription polymerase chain reaction also identified NDV in the specimen. Conclusions: Newcastle conjunctivitis has not been reported for more than 40 years. Mixed infections, including zoonotic pathogens, may be more common than realized.